Archives, race, class and rage. (April 2017) - Prescod, Colin
This is an edited version of a keynote speech to the annual conference of the Archives and Records Association 2016 in which a leading black British cultural curator, using the concept of 'reparative histories', charts his own involvement in and knowledge of recent milestones in black cultural heritage intervention in the UK. Referencing the London Mayor's Commission on African and Asian Heritage, the museum world's marking of the '2007 bi-centenary of the Act abolishing the Atlantic slave trade' and the significant 'No Colour Bar' archive and art exhibition of 2015, he challenges archivists to understand the issue not as the need to simply 'include' Black experience, but to allow Black agency in the making of the record.